Effects of combination therapy with atenolol and amlodipine on blood pressure control and stroke prevention in stroke-prone spontaneously hypertensive rats - Ling Gang; Liu Ai-jun; Shen Fu-ming; Cai Guo-jun; Liu Jian-guo; Su Ding-feng (Acta Pharmacologica Sinica; Vol 28, No 11 (November 2007): Acta Pharmacologica Sinica, 2016)
Aim: To test the effects of atenolol and amlodipine, either alone or in combination, on blood pressure, blood pressure variability (BPV), baroreflex sensitivity (BRS), and the prevalence of stroke in stroke-prone spontaneously hypertensive rats (SHR-SP). Methods: In the first set of the study, 24 8-month-old, female SHR-SP rats were randomly divided into 3 groups. Blood pressure, heart period, and BRS were determined before and after the intragastric administration of atenolol (10 mg/kg) and amlodipine (1.0 mg/kg), either alone or in combination. In the second set of the study, 40 male and 40 female rats were randomly assigned to 1 of the following 4 groups: control, atenolol (10 mg·kg-1·d-1), amlodipine (1.0 mg·kg-1·d-1), and both (10 male and 10 female in each group). The stroke incident and survival time were recorded. Results: Atenolol and amlodipine, either alone or in combination, significantly decreased blood pressure, with the exception of the amlodipine-induced effect on diastolic blood pressure. Meanwhile, only the combination treatment significantly decreased the BPV levels for the same period. The q-values calculated by the probability sum analysis were 1.17 and 2.67 for systolic and diastolic blood pressure, respectively, and were 2.48 and 2.10 for systolic and diastolic BPV, respectively, following administration. Neither drug exhibited any significant effect on BRS. Atenolol and amlodipine, either alone or in combination, significantly increased the lifespan of SHR-SP, with the best effect elicited by the combination therapy. Conclusion: A significant synergism exists between atenolol and amlodipine in lowering and stabilizing blood pressure in SHR-SP. Combination therapy may be an optimal strategy for the prevention of stroke in hypertension.